A Brief Review on the Evolution of Metallic Dental Implants: History, Design, and Application - Kandavalli, Sumanth Ratna; Wang, Qingge; Ebrahimi, Mahmoud; Gode, Ceren; Djavanroodi, Faramarz; Attarilar, Shokouh; Liu, Shifeng (Frontiers in Materials, 2021)
In recent years, significant advances in the field of medical materials have begun to emerge, especially in the nanotechnology. The modern area of nanostructured implants possesses wide applications in various medical implants including its dental use. Nano-surface functions present substantial resolutions to medical obstacles through improved biomaterial proficiency, innovative dental-implant designs, and surface design procedures, such as nanoscale adhesive surfaces, bio-chemical anodization, and surface modification technique. This work covers dental implant history, nanotechnological advances and its development and includes a description, basic properties, and the related results of composites and surface morphology, and the different types of nanomaterials used in dental implants. Significant attempts have been made over the last few decades to strengthen the osteointegration and to prevent bacterial attachment to the implant surfaces. The micro and nano-topography of the hierarchical surface orchestrate the biological reactions of implants and may solve the problems associated with implant-tissue issues. This research offers a brief description of the nanostructured biomaterials to enhance dental implants’ performance and may open new frontiers in the advancement of implant technology.